Enzyme-catalyzed electron and radical transfer - Holzenburg, A. (Andreas); Scrutton, Nigel S. (Sub-cellular biochemistry ;, 2002)
Dramatic advances have been made in recent years in the field of redox enzymology which has resulted in an increase of research activities. This volume will cover the recent milestone developments in this field by leading experts, uniting theory and experiment, and selecting contributions to illustrate important aspects of the mechanisms of electron and radical transfer in proteins. Features: A demonstration of the key principles controlling biological redox reactions; Experimental studies of `simple' soluble systems in various enzyme familiies to illustrate concepts in the control of electron transfer reactions; Detail of advances made in membrane electron transfer through structural descriptions of key membrane-embedded proteins; Appeal to those interested in the design and use of redox enzymes, from academics to industrialists.